2011
DOI: 10.1353/hrq.2011.0062
|View full text |Cite
|
Sign up to set email alerts
|

Information, Choice and Political Consumption: Human Rights in the Checkout Lane

Abstract: Politically motivated consumption behaviors (such as boycotts) are a significant source of human rights mobilization, yet the roots of individual consumption decisions are under-explored in the human rights literature. This article uses original national survey data to evaluate key factors that influence individual decisions to stop purchasing products for broader social purposes, highlighting the role that personal interest, access to particular types of information, and a sense of efficacy play in shaping th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
6
0
1

Year Published

2013
2013
2023
2023

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 38 publications
1
6
0
1
Order By: Relevance
“…These results are similar to many earlier studies as regards gender (e.g., Koos, 2012;Neilson and Paxton, 2010;Tobiasen, 2005), education (e.g., Berlin, 2011;Ferrer-Fons and Fraile, 2014;Neilson, 2010;Strømsnes, 2005), living area (e.g., Sandovici and Davis, 2010;Strømsnes, 2005), political orientation (e.g., Sandovici and Davis, 2010;Strømsnes, 2005), and donating (Strømsnes, 2005;Tobiasen, 2005), and corroborate earlier findings by suggesting that ethical concerns (Scruggs et al, 2011) play a role in political consumption.…”
Section: Who Are the Buycotting And Boycotting Consumers?supporting
confidence: 91%
See 1 more Smart Citation
“…These results are similar to many earlier studies as regards gender (e.g., Koos, 2012;Neilson and Paxton, 2010;Tobiasen, 2005), education (e.g., Berlin, 2011;Ferrer-Fons and Fraile, 2014;Neilson, 2010;Strømsnes, 2005), living area (e.g., Sandovici and Davis, 2010;Strømsnes, 2005), political orientation (e.g., Sandovici and Davis, 2010;Strømsnes, 2005), and donating (Strømsnes, 2005;Tobiasen, 2005), and corroborate earlier findings by suggesting that ethical concerns (Scruggs et al, 2011) play a role in political consumption.…”
Section: Who Are the Buycotting And Boycotting Consumers?supporting
confidence: 91%
“…Studies in the North and South America and Europe have suggested that low trust in institutions and politics (Echegaray, 2015;Neilson and Paxton, 2010;Scruggs et al, 2011;Tobiasen, 2005;Zhang, 2015) are associated with political consumption. In Neilson's European-wide study (2010), political consumers had lower trust in institutions than non-political consumers (see also Koos, 2012), while Berlin (2011) found in his study in Sweden that low trust in "state performance" in advancing sustainability and high trust in "governmental sustainability institutions" (i.e., environmental agencies and the consumer agency) were associated with political consumption.…”
Section: Explaining Political Consumptionmentioning
confidence: 99%
“…Another limitation of the political consumerism literature is its methodological approach, which is heavily based on survey research (Newman and Bartels, 2011;Scruggs et al, 2011;Shah et al, 2007;Strømsnes, 2009). The inflexibility of surveys make it difficult to gain a more nuanced understanding of political consumer meaning-making, specifically as it relates to consumers intersecting social locations such as race, class, and gender.…”
Section: Political Consumerism and Intersectionalitymentioning
confidence: 99%
“…Products which are manufactured in environmentally damaging ways impose not only negative externalities via pollution, for example, but also invoke normative concerns for the environment. Previous research has documented the sociodemographic characteristics that drive individuals to stop purchasing products for broader environmental concerns (Scruggs et al, 2011), or to start purchasing ethically manufactured products (Starr, 2009). These are actions consumers take to affect environmental and social outcomes and are best described as ethical consumption behaviors.…”
Section: Introductionmentioning
confidence: 99%